Mastering Palo Alto networks : build, configure and deploy network solutions for your infrastructure using features of PAN-OS - Piens, Tom (Expert insight., 2022)
Deploy and manage industry-leading PAN-OS 10.x solutions to secure your users and infrastructure. Palo Alto Networks' integrated platform makes it easy to manage network and cloud security along with endpoint protection and a wide range of security services. This book is an end-to-end guide to configure firewalls and deploy them in your network infrastructure. You will see how to quickly set up, configure and understand the technology, and troubleshoot any issues that may occur. This book will serve as your go-to reference for everything from setting up to troubleshooting complex issues. You will learn your way around the web interface and command-line structure, understand how the technology works so you can confidently predict the expected behavior, and successfully troubleshoot any anomalies you may encounter. Finally, you will see how to deploy firewalls in a cloud environment, and special or unique considerations when setting them to protect resources. By the end of this book, for your configuration setup you will instinctively know how to approach challenges, find the resources you need, and solve most issues efficiently.